Effect of Next-Generation Exome Sequencing Depth for Discovery of Diagnostic Variants - Kyung Kim; Moon-Woo Seong; Won-Hyong Chung; Sung Sup Park; Sangseob Leem; Won Park; Jihyun Kim; KiYoung Lee; Rae Woong Park; Namshin Kim (Genomics & Informatics)
Sequencing depth, which is directly related to the cost and time required for the generation, processing, and maintenance of next-generation sequencing data, is an important factor in the practical utilization of such data in clinical fields. Unfortunately, identifying an exome sequencing depth adequate for clinical use is a challenge that has not been addressed extensively. Here, we investigate the effect of exome sequencing depth on the discovery of sequence variants for clinical use. Toward this, we sequenced ten germ-line blood samples from breast cancer patients on the Illumina platform GAII(x) at a high depth of ~200×. We observed that most function-related diverse variants in the human exonic regions could be detected at a sequencing depth of 120×. Furthermore, investigation using a diagnostic gene set showed that the number of clinical variants identified using exome sequencing reached a plateau at an average sequencing depth of about 120×. Moreover, the phenomena were consistent across the breast cancer samples.